1990
DOI: 10.1002/neu.480210205
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization regulates expression of a synaptic vesicle protein in rat superior cervical ganglia in vitro

Abstract: The role of membrane depolarization in the regulation of expression of a neuron specific protein was evaluated by culturing superior cervical ganglia from neonatal rats in defined medium and manipulating neuronal activity by depolarizing agents. P65 is an integral membrane protein of synaptic vesicles and can be used as a marker for general neuronal maturation. P65 antigen levels were quantified by indirect radioimmunoassay, using monoclonal antibodies. The expression of p65 in ganglion explants increased by 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Deafferentation of the SCG in vivo blocks normal postnatal increases in syt (Greif and Trenchard, 1988). Depolarization of ganglia maintained in explant culture using either the Na ϩ channel ionophore, veratridine (Ver), or elevated potassium produces increases in syt levels (Linderman and Greif, 1990). These studies suggest that activitymediated factors may play critical roles in development and maintenance of synaptic components.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Deafferentation of the SCG in vivo blocks normal postnatal increases in syt (Greif and Trenchard, 1988). Depolarization of ganglia maintained in explant culture using either the Na ϩ channel ionophore, veratridine (Ver), or elevated potassium produces increases in syt levels (Linderman and Greif, 1990). These studies suggest that activitymediated factors may play critical roles in development and maintenance of synaptic components.…”
Section: Introductionmentioning
confidence: 94%
“…Animals were checked at least twice daily to pinpoint the time of birth of pups. Two-day-old pups (with the date of birth designated P0) were anesthetized on ice prior to decapitation and removal of SCGs; previous work indicated that little change in syt occurred during this period in vivo, while ganglia doubled in protein content (Greif and Reichardt, 1982;Linderman and Greif, 1990). …”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations